Genetic Variants of HOTAIR Associated With Colorectal Cancer Susceptibility and Mortality - Kim, Jung Oh; Jun, Hak Hoon; Kim, Eo Jin; Lee, Jeong Yong; Park, Han Sung; Ryu, Chang Soo; Kim, Seungki; Oh, Doyeun; Kim, Jong Woo; Kim, Nam Keun (Frontiers in Oncology, 2020)
In colorectal carcinogenesis, the unique molecular and genetic changes that occur within cells result in specific CRC phenotypes. The involvement of the long non-coding RNA, HOTAIR, in cancer development, progression, and metastasis is well established. Various studies have reported on the contribution of HOTAIR to cancer pathogenesis. Therefore, we selected four HOTAIR polymorphisms (rs7958904G>C, rs1899663G>T, rs4759314A>G, and rs920778T>C) to evaluate the association of each variant with CRC prevalence and prognosis. We conducted a case–control study of 850 individuals to identify the genotype frequencies of each polymorphism. The study population included 450 CRC patients and 400 control individuals that were randomly selected following a health screening. Notably, rs7958904 and rs1899663, their hetero genotype, and the dominant model were significantly different when compared to the healthy control group (rs7958904; AOR=1.392, 95% CI=1.052–1.843, P=0.021). To evaluate the effect of HOTAIR polymorphisms on survival rate, we analyzed patient mortality and relapse occurrence within 3 and 5 years with Cox-regression analysis. The rs7958904 CC polymorphism mortality rate was significantly higher than the GG polymorphism mortality rate (adjusted HR=2.995, 95% CI=1.189–7.542, P=0.021). In addition, the rs920778 CC genotype was significantly different than the TT genotype (adjusted HR=3.639, 95% CI=1.435–9.230, P=0.007). In addition, this study confirmed that genetic variants of HOTAIR alter the mRNA expression level (P <0.01). We suggest that HOTAIR rs7958904G>C which is associated with CRC prevalence and mortality is a potential biomarker for CRC. The association between HOTAIR gene polymorphisms and CRC prevalence were reported for the first time.